Tantangan Pesantren Salaf dan Khalaf di Era Global - Yayat Hidayat; Hadiat Hadiat; Mohamad Yudiyanto; Peri Ramdani (Jurnal Ilmiah Wahana Pendidikan, 2022)
This paper intends to show the various challenges of salaf (traditional) and khalaf (modern) pesantren in the era of globalization. Islamic boarding schools, both salaf and khalaf, are faced with multiple problems. Problems that arise from the internal side as well as from the external environment. On the one hand, the pesantren must produce people who are religious experts, on the other hand, its output can compete with the demands and demands of the times. The research method used is library research (library research). Sources of data are taken from books, journals, and other information sourced from electronic media. The challenges faced by pesantren include: 1) micro: sources of funds, infrastructure, Kiai authority, and learning patterns. 2) macro: materialism, hedonism and individualism. These challenges, both micro and macro in nature, can be used as a barometer, because it is considered important to maintain this Islamic educational institution, namely the pesantren, as an educational institution that survives